(untitled) (Journal of Universal Science Research, 2026)
The rapid development of non-state educational organizations has intensified the need for highly qualified pedagogists capable of adapting to innovative teaching methodologies, digital technologies, and market-driven educational demands. This article examines existing mechanisms for improving the professional qualifications of pedagogists in non-state educational institutions and identifies key shortcomings in their implementation. Based on a systematic analysis, the study proposes an improved mechanism focused on continuous professional development, competency-based training, institutional autonomy, and digital learning platforms. The findings contribute to the development of a sustainable model for enhancing pedagogical quality in non-state education.